Blood-based DNA methylation profiles in major depressive disorder, bipolar disorder, and schizophrenia spectrum disorders - David, Friederike S.; Frank, Josef; Stein, Frederike; Meinert, Susanne; Zillich, Lea; Sirignano, Lea; Streit, Fabian; Beins, Eva C.; Sindermann, Lisa; Usemann, Paula; Goltermann, Janik; Leehr, Elisabeth J.; et al. (Comprehensive psychiatry, 2025)
Alterations in DNA methylation (DNAm) profiles have been implicated in affective and psychotic disorders. However, no comprehensive understanding of peripheral DNAm profiles associated with diagnostic groups, course of illness, and other clinical variables has emerged yet. In particular, studies exploring commonalities and differences across diagnoses are lacking. Here we conducted a systematic epigenetic characterization of the transdiagnostic German FOR2107 cohort, including individuals with major depressive disorder (MDD, n = 342), bipolar disorder (BD, n = 99), or a schizophrenia spectrum disorder (SSD, n = 101) and healthy controls (HC, n = 339). For 183 MDD cases and 178 HC, we assessed additional DNAm data from the two-year follow-up study visit. To explore DNAm differences between and across diagnostic groups, case-control and case-case methylome-wide association studies were performed. Our sample was further characterized using methylation risk scores (MRS) for MDD and SSD. Finally, epigenetic age acceleration was examined and compared to a measure of brain age acceleration. We identified few methylome-wide significant associations with diagnostic groups. MRS for MDD did not differ between diagnostic groups, and an increase in MRS for SSD in SSD compared to HC did not remain significant when adjusting for smoking behavior and BMI. An increase in epigenetic age acceleration was most evident for SSD compared to HC, which did not remain significant when adjusting for covariates. No correlation between epigenetic and brain age acceleration was observed. Our findings emphasize the relevance of potential confounding factors in epigenetics research in psychiatry and contribute to a growing body of studies on DNAm profiles across affective and psychotic disorders.
Gesehen am 04.12.2025